Komik Berbasis Scientific Sebagai Media Pembelajaran di Masa Pandemik Covid-19 - Very Hendra Saputra Very; Donaya Pasha (SJME (Supremum Journal of Mathematics Education), 2021)
This study aims to determine the development of instructional media that can help teachers and students in the learning process, as well as parents in accompanying students to study at home during the Covid-19 pandemic. The development method used is Research and Development with 4D designs, and media design using comic life. To test the validity of the media being developed, validation is carried out regarding the material and design as well as technical quality testing. This research succeeded in developing comic learning media based on the scientific approach for grade IV students on rectangular circumference material. The percentage of validation tests for material experts and media experts was 81.667% and 83.571%, and the results of technical quality tests were 86.428%. This shows that the media developed is suitable for use as a learning medium.